Hubungan Antara Self-Regulated Learning Dengan Prokrastinasi Akademik Siswa - Dirga Assafi’i; Arman Bin Anuar; Nur Saqinah Galugu; Abdul Kadir (Jurnal Bimbingan dan Konseling Ar-Rahman, 2023)
This research aims to ascertain the association between self-regulated learning and student academic procrastination in class XI SMAN 11 Luwu Utara in light of the phenomenon of students spending a lot of time exclusively on entertainment things rather than academic problems. This research employs a sample of 50 class IX students who specialize in science and social studies and who completed authentic and trustworthy questionnaires. It is quantitative in nature and is of the correlational kind. With the aid of SPSS 26.0 for Windows, two types of analysis—descriptive and inferential—were used to analyze the data. The study's findings indicate a significant negative linear relationship between the variables self-regulated learning (X) and academic procrastination (Y), with a large relationship between the two of -47.5%, which indicates that there is a negative relationship between the two in class XI students of SMAN 11 Luwu Utara at a moderate level and the remaining 34.9% is the remaining variable. Students' ability to learn independently decreases when academic procrastinating behavior increases, and vice versa. The next research can therefore test the effectiveness of interventions aimed at enhancing Self-Regulated Learning and reducing students' academic procrastination.._____________________________________________________________ Sepanjang sepuluh tahun kebelakangan ini, telah didapati banyak siswa menghabiskan lebih banyak waktu untuk hiburan daripada bidang akademik sehingga  objektif kajian ini adalah untuk menentukan hubungan antara self-regulated learning dan prokrastinasi akademik siswa pada kelas XI SMAN 11 Luwu Utara Penyelidikan ini menggunakan pendekatan kuantitatif jenis korelasional. Sampelnya terdiri daripada 50 pelajar peminat IPA dan IPS dari kelas IX, yang mengisi angket yang telah valid dan realiabel. Analisis deksriptif dan inferensial berbantuan termasuk dalam SPSS 26.0 untuk Windows digunakan pada peneliitanini. Hasil kajian menunjukkan bahawa variabel Self-Regulated Learning (X) dan Prokrastinasi Akademik (Y) mempunyai hubungan linear negatif secara signifikan, dengan besar hubungan Self-Regulated Learning terhadap prokrastinasi akademik sebesar -47,5 %. Ini menunjukkan bahwa terdapat hubungan yang cukup negatif antara prokrastinasi akademik dengan Self-Regulated Learning pada siswa kelas XI SMAN 11 Luwu Utara. Sisanya sebesar 34,9% disebabkan oleh hubungan dengan variabel di luar penelitian, sehingga semakin banyak perilaku prokrastinasi akademik yang dilakukan, maka Self-Regulated Learning siswa akan semakin rendah, begitu pula sebaliknya. Dengan demikian penelitian selanjutnya dapat menguji efektivitas intervensi yang bertujuan untuk meningkatkan Self-Regulated Learning dan mengurangi prokrastinasi akademik siswa.